Gonadal hormones and metabolic syndrome in middle-aged and elderly males: results from a prospective cohort study in China - Zhang, Zhuo; Chen, Yingna; Li, Na; Huang, Chulin; Lin, Diaozhu; Wang, Chengzhi; Wang, Chunying; You, Lili; Li, Lingling; Li, Fangping; Liang, Ying; Xiao, Huisheng; et al. (Frontiers in Endocrinology, 2024)
Researches have shown that gonadal hormones are involved in metabolic pathways relevant to metabolic syndrome (MetS). Nevertheless, no longitudinal study has been conducted on the association between SHBG and MetS in Chinese. The objective of our study was to determine whether there is any association among middle-aged and elderly males in China. A total of 531 eligible male subjects, aged above 40 years or older, without MetS at baseline, were recruited. Sex hormone binding globulin (SHBG), total testosterone (TT), follicle-stimulating hormone (FSH), and luteinizing hormone (LH) were measured. A harmonized definition and recommended thresh-olds for the Chinese population were used to determine metabolic syndrome. During 3.2 years of follow-up, 20.7% of subjects had developed MetS. Compared with the non-MetS group, subjects in the newonset MetS group had significantly lower SHBG (53.7nmol/L [33.8, 115.0] vs 43.5 nmol/L [28.8, 74.9], P=0.0018), TT (19.